Recovery with a fan-cooling jacket after exposure to high solar radiation during exercise in hot outdoor environments - Naito, Takashi; Saito, Tatsuya; Ohhashi, Mitsunori; Hayashi, Sotaro (Frontiers in Sports and Active Living, 2023)
The study aimed to investigate the effect of body cooling with a fan-cooling jacket on body temperature responses during recovery after exercise when exposed to high solar radiation in a hot outdoor environment. Nine males cycled using ergometer until their rectal temperature increased to 38.50 °C in hot outdoor environments, followed by body cooling recovery in warm indoor environments. Subjects repeatedly performed the cycling exercise protocol, which consisted of one set of 5 min at a load of 1.5 watt/kg body weight and 15 min at a load of 2.0 watt/kg body weight at 60 rpm. Body cooling recovery consisted of cold water ingestion (10°C: CON) or cold water ingestion + wearing a fan-cooling jacket (FAN) until the rectal temperature decreased to 37.75°C. The time for the rectal temperature to reach 38.5°C did not differ between the two trials. The rate of decrease in rectal temperature at recovery tended to be higher in FAN trial than in CON trial (P = 0.082). The rate of decrease in tympanic temperature was higher in FAN trials than in CON trials (P = 0.002). The rate of decrease in mean skin temperature at the first 20 min of recovery was higher in FAN than in CON trial (P = 0.013). Body cooling recovery with a fan-cooling jacket in addition to cold water ingestion may be effective in reducing elevated tympanic and skin temperatures after exercise in the heat under a clear sky, but may be difficult to decrease rectal temperature.